Concurrent Clostridial Enteritis and Oviductal Adenocarcinoma with Carcinomatosis in an Adult Alpaca (Vicugna pacos). (November 2021) - Womble, Mandy; Schreeg, Megan E.; Hoch, Allison; de Souza Meira, Enoch B.; Foster, Derek; Premanandan, Christopher; Negrão Watanabe, Tatiane T.
Summary: An adult alpaca ( Vicugna pacos ) with a history of colic and anorexia was euthanized because of failure to respond to treatment. Macroscopically, pale-tan, multifocal to coalescing, firm nodules and plaques markedly expanded the omentum, mesentery and the parietal and visceral peritoneum of multiple abdominal organs, especially the right oviduct and associated mesosalpinx. Abundant dark-red watery digesta were present in the duodenum and jejunum. Histological evaluation of the right oviduct, abdominal visceral nodules and plaques and mesenteric lymph nodes revealed transmural expansion and replacement by an epithelial malignant neoplasm, comprised of tubules and acini of ciliated columnar cells supported by abundant fibrous connective tissue. Both ovaries were histologically normal. On the basis of the ciliated morphology of the neoplastic cells, the focus on the proximal reproductive tract and the unremarkable ovaries, a reproductive tubal adenocarcinoma with carcinomatosis was diagnosed, with both the endometrium and oviduct considered as the tissues of origin. The prominent ciliated morphology of the neoplastic cells and the classification of human fallopian tube (oviduct) neoplasia lead us to propose oviductal adenocarcinoma with widespread carcinomatosis as the definitive diagnosis. The lamina propria of the small intestine was infiltrated segmentally by lymphocytes, plasma cells and neutrophils, and Clostridium perfringens with beta2 toxin production was identified by polymerase chain reaction in the small intestinal contents. To our knowledge, this is the first report of these two distinct diseases in an alpaca.